Practices in delivery and birth care from mothers’ perspective - Débora Apolinário; Marcelexandra Rabelo; Lillian Daisy Gonçalves Wolff; Silvana Regina Rossi Kissula Souza; Giseli Campos Gaioski Leal (Rev Rene)
Objective: to highlight the practices of delivery and birth care in a maternity ward from mothers’ perspective. Methods: descriptive cross-sectional study with a quantitative approach carried out in a maternity hospital of usual risk, with 100 regular postpartum mothers. It was used a semi-structured questionnaire as recommended by the World Health Organization. Results: among the practices that should be encouraged from birth care, stands out: women’s privacy; participation of the companion of their choice; the use of non-pharmacological methods for pain relief. Among the practices that should be eliminated: the transfer to the delivery room at the second stage and the lithotomy position. Conclusion: women are still passive in the birth process despite attempts to change the model of care during labor and birth.